Zero budget natural farming components Jeevamrit and Beejamrit augment Spinacia oleracea L. (spinach) growth by ameliorating the negative impacts of the salt and drought stress - Patel, Margi; Islam, Shaikhul; Glick, Bernard R.; Choudhary, Nisha; Yadav, Virendra Kumar; Bagatharia, Snehal; Sahoo, Dipak Kumar; Patel, Ashish (Frontiers in Microbiology, 2024)
The growth of crop plants, particularly spinach (Spinacia oleracea L.), can be significantly impeded by salinity and drought. However, pre-treating spinach plants with traditional biofertilizers like Jeevamrit and Beejamrit (JB) substantially reverses the salinity and drought-induced inhibitory effects. Hence, this study aims to elucidate the underlying mechanisms that govern the efficacy of traditional fertilizers. The present work employed comprehensive biochemical, physiological, and molecular approaches to investigate the processes by which JB alleviates abiotic stress. The JB treatment effectively boosts spinach growth by increasing nutrient uptake and antioxidant enzyme activity, which mitigates the detrimental effects of drought and salinity-induced stress. Under salt and drought stress conditions, the application of JB resulted in an impressive rise in germination percentages of 80% and 60%, respectively. In addition, the application of JB treatment resulted in a 50% decrease in electrolyte leakage and a 75% rise in the relative water content of the spinach plants. Furthermore, the significant reduction in proline and glycine betaine levels in plants treated with JB provides additional evidence of the treatment's ability to prevent cell death caused by environmental stressors. Following JB treatment, the spinach plants exhibited substantially higher total chlorophyll content was also observed. Additionally, using 16S rRNA sequencing, we discovered and characterized five plant-beneficial bacteria from the JB bio-inoculants. These bacterial isolates comprise a number of traits that contribute to growth augmentation in plants. These evidences suggest that the presence of the aforesaid microorganisms (along with additional ones) is accountable for the JB-mediated stimulation of plant growth and development.